Viola seed pod architecture shapes sequential, force-augmented pinching - Cheongsan Kim; Jihyun Won; Donghyeon Kim; Sohyun Jung; Ho-Young Kim; Youbong Hyun (Science, 2026)
Many plants explosively launch seeds, but these natural catapults often display inefficient, unpredictable energy transfer in seed ejection. Violets ( Viola spp.) address this problem by ejecting seeds successively with consistent propulsive force from a single pod, a strategy that requires sophisticated energy release. In this work, we show that Viola achieves this feat with a simple and compact structure that generates adaptive force augmentation through sequential pinching. Our biological and mathematical analyses indicate that the pod valve’s morphogeometry optimizes pinching with sufficient strength for seed ejection with limited material cost and creates a shifting force-amplifying hotspot, which allows consecutive seed ejections. We use this design principle to create autonomous zipping actuators for a range of applications, including biomedical soft machines.